2019
DOI: 10.1038/s41467-019-08497-3
|View full text |Cite
|
Sign up to set email alerts
|

High temperature singlet-based magnetism from Hund’s rule correlations

Abstract: Uranium compounds can manifest a wide range of fascinating many-body phenomena, and are often thought to be poised at a crossover between localized and itinerant regimes for 5f electrons. The antiferromagnetic dipnictide USb2 has been of recent interest due to the discovery of rich proximate phase diagrams and unusual quantum coherence phenomena. Here, linear-dichroic X-ray absorption and elastic neutron scattering are used to characterize electronic symmetries on uranium in USb2 and isostructural UBi2. Of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 34 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…In fact, recent DFT + DMFT calculations that evaluated the competition between local moment physics and electronic itinerancy found that the f 1 and f 3 states contribute approximately 25%, which is significantly less than observed in our data, but does support the idea of the multiconfigurational nature of actinide materials. [25] The measured f -occupation just below n f =2 at the lowest measured pressure is consistent with ambient pressure angle-resolved photoemission spectroscopy data that suggests some of the f -electrons have hybridized with the conduction band. [26] As the lattice contracts, this hybridization strengthens, causing the f -occupation to decrease as a function of pressure.…”
Section: Discussionsupporting
confidence: 78%
“…In fact, recent DFT + DMFT calculations that evaluated the competition between local moment physics and electronic itinerancy found that the f 1 and f 3 states contribute approximately 25%, which is significantly less than observed in our data, but does support the idea of the multiconfigurational nature of actinide materials. [25] The measured f -occupation just below n f =2 at the lowest measured pressure is consistent with ambient pressure angle-resolved photoemission spectroscopy data that suggests some of the f -electrons have hybridized with the conduction band. [26] As the lattice contracts, this hybridization strengthens, causing the f -occupation to decrease as a function of pressure.…”
Section: Discussionsupporting
confidence: 78%
“…This is the essential idea of Mott physics or Mottness [4,6]. Even though many correlated electron materials are far away from the Mott insulating state and the Coulomb repulsion U is moderate, strong electron correlation is still observed experimentally [7,8]. In that case, Hund's rule coupling J H , which favors to align the spins in different orbitals, provides an alternative way to yield electron correlation [9].…”
mentioning
confidence: 99%
“…Further theoretical studies show that other topological phases, including non-Fermi liquid topological phases, can be driven by the Kondo effect combined with crystalline symmetries 22 , 23 . Note that in the magnetically ordered systems, Kondo hybridization gives rise to non-symmetry-breaking low-temperature coherence phenomena, which are not precluded by the high transition temperature 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%